Eliciting information from a committee - Andriy Zapechelnyuk (Queen Mary University of London, School of Economics and Finance, 2012)
The paper addresses the mechanism design problem of eliciting truthful information from a committee of informed experts who collude in their information disclosure strategies. It is shown that under fairly general conditions full information disclosure is possible if and only if the induced outcome is Pareto undominated for the committee members.
Keywords: D82; C78; D72; 330; Communication; Multidimensional mechanism design; Experts; Collusion; Axiomatic bargaining; Closed rule